2013
DOI: 10.33549/physiolres.932598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methamphetamine on Cognitive Functions of Adult Female Rats Prenatally Exposed to the Same Drug

Abstract: The aim of this study was to investigate the effect of prenatal methamphetamine (MA) exposure and application of the same drug in adulthood on cognitive functions of adult female rats. Animals were prenatally exposed to MA (5 mg/kg) or saline (control group). The cognitive function was tested as ability of spatial learning in the Morris Water Maze (MWM). Each day of the experiment animals received an injection of MA (1 mg/kg) or saline. Our results demonstrated that prenatal MA exposure did not affect the late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Nevertheless, previous investigations have recommended that while the acute use of Meth may enhance memory and attention, chronic use results in reduced memory function ( Seminerio et al, 2013 ). It has been reported that exposure to Meth during preadolescence improves spatial learning in male rats ( Macúchová et al, 2013 ). Surprisingly, clinical studies have also declared that Meth can result in improved learning and memory function, including visuospatial perception and response speed following limited stimulant usage ( Braren et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, previous investigations have recommended that while the acute use of Meth may enhance memory and attention, chronic use results in reduced memory function ( Seminerio et al, 2013 ). It has been reported that exposure to Meth during preadolescence improves spatial learning in male rats ( Macúchová et al, 2013 ). Surprisingly, clinical studies have also declared that Meth can result in improved learning and memory function, including visuospatial perception and response speed following limited stimulant usage ( Braren et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Meth reduced the intraneuronal oxidative metabolism of dopamine by the repression of monoamine oxidase ( Pereira et al, 2011 ). Also, acute administration of Meth caused an increase in the dopamine level in the nucleus accumbens ( Macúchová et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average swim path length moved by the rats that received all doses of khat extract and juice subchronically was significantly greater than the rats that received the vehicle. Previous studies indicated that rats that received cocaine (3) and amphetamine (24 & 25) swam longer pathlength compared with control before rats escaped into the hidden platform. Tukey’s test also showed that rats that received the lower dose of extract subchronically had a significantly greater speed than rats that received the middle dose of the extract and vehicle that could be attributed to khat-induced neurochemical alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have described various sequelae related to prenatal MA exposure. Our previous studies have demonstrated that prenatal drug exposure can impair sensorimotor development ( Šlamberová et al, 2006 ; Holubová et al, 2017 ) as well as the development of the central nervous system of rat pups and induce various psychological impairments ( Šlamberová, 2012 ; Macúchová et al, 2013 ). Although it was shown that prenatal MA exposure could induce changes affecting behavior during the preweaning period, these changes did not seem to persist into adulthood ( Hrubá et al, 2010 , 2012 ).…”
Section: Introductionmentioning
confidence: 99%